Desempeño laboral del área operativa de BanEcuador de la ciudad de Babahoyo. - Bastidas García, Nayeli Nicole (2022)
During the last years, labor performance has become a fundamental element within the organizations, the collaborators are the most valuable and indispensable within the company, they allow a good functionality and development of the activities that they carry out in any institution. Job performance refers to the quality of the service or work performed by the employee within the organization. Here come into play from their professional skills to their interpersonal skills and directly affect the results. However, currently companies forget how important are the employees and their good quality of work for the company to achieve its objectives as is the case of BanEcuador which is located in the city of Babahoyo, between Malecon and Eloy Alfaro, according to the respective investigation it was found that there is a lack of trained personnel, conditioning of the workplace, outdated and obsolete work equipment, which are important factors for the proper performance of daily activities within the financial organization.